Keterlibatan Generasi Z dalam Melestarikan Cagar Budaya Prasasti Mantyasih melalui Konten Tiktok Sejarah - Ayun, Khuroto; Saputro, Pradata ardi (Jurnal Pendidikan Sejarah Indonesia, 2025)
Modernization influences the quality of the younger generation in their actions and behavior. The loss of Generation Z’s awareness of their cultural heritage has become an important concern that requires proper solutions. Historical values contained in every cultural heritage site must continue to be preserved to maintain their sustainability. In the era of revolution, developments in information and technology are advancing rapidly. One example is a social media platform called TikTok. The TikTok application has been downloaded by millions of users from various countries. TikTok provides diverse video features that are easily accessible to anyone. Therefore, educational content is needed to stimulate curiosity among the younger generation. In fact, the current habit of the younger generation is scrolling through TikTok and other social media platforms. The presence of educational historical content, such as cultural heritage, can help improve Generation Z’s knowledge and encourage their participation in preserving cultural heritage. Indonesia has various historical sites that have been recognized by UNESCO. This study takes the Mantyasih Inscription located in the Magelang City area as the research object.